2021
DOI: 10.3390/su13137277
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Outbreak of the COVID-19 Pandemic on Formal and Informal Care of Community-Dwelling Older Adults: Cross-National Clustering of Empirical Evidence from 23 Countries

Abstract: The COVID-19 pandemic has been dramatically affecting the life of older adults with care needs and their family caregivers. This study illustrates how the initial outbreak of the pandemic changed the supply of formal and informal care to older adults in European countries and Israel and assesses the resilience of these countries in providing support to their older populations by means of a mix of both types of care. We subjected data from the Survey of Health, Ageing and Retirement in Europe COVID-19 period (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 39 publications
2
29
2
Order By: Relevance
“…Thus, the study confirms the lower resilience of the Italian formal and informal care supports in response to the reduction of the care services during the pandemic compared to Germany [63]. In addition, this study identifies MCWs as one of the main sources of resilience in the German and Italian LTC systems and advances further hypotheses for the interpretation of the results coming from previous and future studies focusing on the response of the LTC systems to the challenges posed by the COVID-19 health crisis.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Thus, the study confirms the lower resilience of the Italian formal and informal care supports in response to the reduction of the care services during the pandemic compared to Germany [63]. In addition, this study identifies MCWs as one of the main sources of resilience in the German and Italian LTC systems and advances further hypotheses for the interpretation of the results coming from previous and future studies focusing on the response of the LTC systems to the challenges posed by the COVID-19 health crisis.…”
Section: Discussionsupporting
confidence: 74%
“…This study, which reached an overall sample of 2468 European caregivers from 16 countries, is focused on two sub-samples of 146 informal caregivers living in Germany and 173 in Italy, providing care to older people aged 65 and over having LTC needs (i.e., experiencing multiple chronic diseases limiting their activities of daily living). Since several studies have analysed the consequences of the first pandemic wave in Spring 2020 [46][47][48][49][50][51][52][59][60][61][62][63], an added value of the study is that it provides evidence about the impact of the COVID-19 outbreak in winter 2020-2021, a critical period in which the effects of the first and following pandemic waves in Europe may have cumulated over time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from various countries show that gender (Lorenz‐Dant & Comas‐Herrera, 2021 ; Raiber & Verbakel, 2021 ; Zwar et al, 2022 ), age (Budnick et al, 2021 ; Hofstaetter et al, 2022 ), employment (Truskinovsky et al, 2022 ), living situation of the care recipient (Prins et al, 2021 ; Smaling et al, 2022 ), relationship to the care recipient (Tur‐sinai et al, 2021 ) and network (Allen et al, 2022 ) were important characteristics that distinguish how caregivers were affected. Studies in the Netherlands found that there were differences between men and women, and between those in different relationships to the care recipient (Prins et al, 2021 ; Raiber & Verbakel, 2021 ; Smaling et al, 2022 ; Tur‐sinai et al, 2021 ) Previous literature thus shows that consequences differed across countries, which may be due to differences in measures, COVID impact and healthcare system (Lorenz‐Dant & Comas‐Herrera, 2021 ; Santini et al, 2022 ; Tur‐sinai et al, 2021 ). In the Netherlands, there were relative large increases in informal care and decreases in formal care compared to other countries (Tur‐sinai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the Netherlands found that there were differences between men and women, and between those in different relationships to the care recipient (Prins et al, 2021 ; Raiber & Verbakel, 2021 ; Smaling et al, 2022 ; Tur‐sinai et al, 2021 ) Previous literature thus shows that consequences differed across countries, which may be due to differences in measures, COVID impact and healthcare system (Lorenz‐Dant & Comas‐Herrera, 2021 ; Santini et al, 2022 ; Tur‐sinai et al, 2021 ). In the Netherlands, there were relative large increases in informal care and decreases in formal care compared to other countries (Tur‐sinai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%